Tampon Pulpotomy: Long-term Successful Results of a Molar with Irreversible Pulpitis and Previous Vital Pulp Therapy Failure - Asgary , Saeed; Roghanizadeh , Leyla (Iranian Endodontic Journal, 2023)
Minimally invasive vital pulp therapy (VPT) techniques have become increasingly popular for treating mature permanent teeth with irreversible pulpitis. However, in cases where less invasive VPT approaches, such as miniature pulpotomy, fail to provide symptom relief and desired outcomes, alternative treatment strategies need to be explored. This case report presents the successful application of tampon pulpotomy, a modified full pulpotomy technique, in a vital molar tooth with irreversible pulpitis, after a previous miniature pulpotomy failure. The tampon pulpotomy procedure involved the placement of an endodontic biomaterial (i.e. calcium-enriched mixture cement) over the pulpal wound to stop bleeding and create a favorable environment for pulpal healing/regeneration. The patient was followed up for a period of 10 years, during which the tooth remained asymptomatic, functional, and exhibited normal periodontal ligament. This case report highlights the potential effectiveness of tampon/full pulpotomy as a retreatment option in cases where more conservative VPT techniques have shown limited success, offering a conservative approach to preserve tooth structure and pulpal vitality.